Ecology of War, Health Research and Knowledge Subjugation: Insights from the Middle East and North Africa Region. Issue 1 (18th September 2020) - El Achi, Nassim; Menassa, Marilyne; Sullivan, Richard; Patel, Preeti; Giacaman, Rita; Abu-Sittah, Ghassan S.; ,
In an ecology of war, as experienced in the Middle East and North Africa region, health research faces several interrelated challenges: de-prioritization, paucity in the generation of reliable data, and its securitization. This directly contributes to local knowledge subjugation and research waste as local narratives are disqualified in favor of institutionalized and privileged global unitary knowledge. Huge efforts that require political will and commitment, coupled with multidisciplinary approaches and sustainable collaborations between researchers and humanitarian workers at the local, regional and global levels, are indispensable to give more space for the abandoned local knowledge in order to have contextualized and more impactful interventions where more lives are saved.